Bagaimana Konstruksi Program Marketing Mix Produk-produk Halal ? - Salihah Khairawati (Pusat Studi Ekonomi Islam Sekolah Tinggi Ekonomi Islam Hamfara, 2018)
The role of marketing is very important for the company. Marketing contributes to product success in the market. The company will arrange a marketing mix to gain a competitive advantage. Products labeled as halal are currently experiencing growth in consumption levels both nationally and globally. Products labeled as halal are currently consumed by various groups, especially Muslims. Interestingly, Muslims have guidelines for consumption that marketers need to pay attention. The guideline is closely related to the rules and principles of belief based on Islamic sharia. It is not enough that marketers display halal labels on their products, but the marketing mix is aligned with Islamic sharia principles so that consumers can be well appreciated.